Proceedings, high altitude revegetation workshop no. 3 - Kenny, Stephen T., editor; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1978)
The 3rd high altitude revegetation workshop was held on March 13-14, 1978 at Colorado State University in Fort Collins, Colorado.
Workshop cosponsors, Climax Molybdenum Company, AMAX ... [et al.].
Keywords: Revegetation -- Congresses; Mountain plants -- Congresses; Reclamation of land -- Congresses